LEXICAL-GRAMMATICAL FEATURES OF PHRASAL VERBS IN ENGLISH AND PROBLEMS OF THEIR RENDERING IN UZBEK - Nazarova Komola Anvarovna (Journal of new century innovations, 2024)
Annotation: This thesis investigates the intricate lexical-grammatical features of verb phrases in English, focusing on verb forms, auxiliaries, modals, particles, and complements, and delves into the challenges encountered in translating these structures into Uzbek.